Diverse roles of lung macrophages in the immune response to influenza A virus - Li, Haoning; Wang, Aoxue; Zhang, Yuying; Wei, Fanhua (Frontiers in Microbiology, 2023)
Influenza viruses are one of the major causes of human respiratory infections and the newly emerging and re-emerging strains of influenza virus are the cause of seasonal epidemics and occasional pandemics, resulting in a huge threat to global public health systems. As one of the early immune cells can rapidly recognize and respond to influenza viruses in the respiratory, lung macrophages play an important role in controlling the severity of influenza disease by limiting viral replication, modulating the local inflammatory response, and initiating subsequent adaptive immune responses.However, influenza virus reproduction in macrophages is both strain-and macrophage type-dependent, and ineffective replication of some viral strains in mouse macrophages has been observed. This review discusses the function of lung macrophages in influenza virus infection in order to better understand the pathogenesis of the influenza virus.